Peranan Public Relations dalam Rebranding TVRI untuk Membentuk New Image - Meinati Fajar Rizki (Program Studi Ilmu Komunikasi FISIP Universitas Syiah Kuala, 2019)
Indonesian state-run television (TVRI) is a state-owned public broadcasting institution that aired since August 24, 1962. However, along with media development, TVRI has been largely abandoned by Indonesians. The 'outdated' image is attached to TVRI due to various factors, such as the program view, the image quality, and the logo. In March 2019, LPP TVRI conducted a comprehensive rebranding program by introducing its new logo and slogan. The purpose of this study is to explore the role of the Public Relations of LPP TVRI in this rebranding activity to change the image of 'outdated' into up-to-date television. Data were collected through interviews with three Public Relations staff and two audiences of LPP TVRI. In the process of rebranding, LPP TVRI employed renaming because there was no change in name, but only a change of logo and slogan as 'unifying media', cooperating with DM ID brand consultants in its process. The results of this study showed that in this regard, LPP TVRI Public Relations has played four roles, including Expert Prescriber, Communication Facilitator, Problem Solver Facilitator, and Communication Technical. The roles of Expert Prescriber and Communication Facilitator need to be improved for the rebranding process.